SELECTION PROCESS AND TEACHERS’ JOB PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN OSUN STATE, NIGERIA - Ibrahim, Muinat Abiodun; Adebayo, Monsurat Folake (African Journal of Educational Management, 2023)
The study investigated the influence of selection process on job performance of teachers in public secondary schools in Osun State, Nigeria. It adopted the quantitative research design. The population of the study comprised of 3,546 teachers in 364 senior secondary schools in Osun State, out of which 569 were selected using multi-stage sampling procedure. A self-designed instrument was used for data collection. A test re-test method was used for the reliability of the instrument with a coefficient of 0.766. Two hypotheses were formulated and tested with regression analysis and both hypotheses were significant at 1 percent level of significance. Findings of the study revealed that teacher’s qualifications and placement influence teachers’ performance in schools in Osun State. Based on the findings, the study recommended that government follow due process in employing qualified teachers and teachers should be made to teach subjects only in their subject area, for better learning outcome.